A history of the art of war in the Middle Ages - Oman, Charles, 1860-1946. (London : Greenhill Books ; Mechanicsburg, PA, USA : Stackpole Books, 1998)
"Each section deals with the characteristic strategy, tactics, and military organisation of a period and illustrates them by detailed accounts of typical battles and campaigns."
V. 1. 378-1278 A.D. -- v. 2. 1278-1485 A.D.
Originally published: London, Methuen & co. ltd., 1924.
Includes bibliographical references and index.
Keywords: Military art and science -- History; Military history, Medieval; History